Analysis of Mulching Effects on The Growth Performence of Spring Onion Freda Variety (Allium fistulosum L.) - Novani Wahyu Christanti; Nugraheni Widyawati (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2022)
The use of mulch aims, among others, to provide a more ideal microclimate to support the growth of spring onion. The purpose of this study was to analyze the effect of mulch on the growth performance of the spring onion Freda Variety. The research location was conducted at the Salaran Experimental Garden belonging to the SWCU Agriculture and Business Faculty from May 2021 to August 2021. This experiment used RAK which consisted of five treatments, namely M0 (without mulch), M1 (black-silver plastic mulch), M2 (transparent plastic mulch), M3 (corn stem mulch), M4 (reed mulch). Each treatment was repeated five times and the data were analyzed using variance and DMRT 5%. The result showed that the best treatment to support spring onion performance was reed mulch because it had the highest average of all growth components and plant fresh weight of 53,17 cm, stem diameter 14,92 mm, number of leaves 6,50 leaves, number of tillers 1,90 and fresh weight 441 grams and has the highest soil organic matter content, lower temperature soil and increase soil moisture. Keyword: Reed, Corn stem, Spring onion, Plastic mulch, Mulching